2003
DOI: 10.1515/znc-2003-7-815
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Methylphenone Derivatives and 5-Methylcoumarins from Mutisia friesiana

Abstract: In addition to the known mutisicoumarin A, the aerial parts of the shrub Mutisia friesiana afforded five new methylphenones, two new 5-methylcoumarins and a new related chromone. Their structures were elucidated by spectroscopic methods. 13C NMR data for mutisicoumarin A are reported for the first time. Mutisiphenones A and B and mutisicoumarin A showed antifungal activity against the phytopathogenic fungus Cladosporium cucumerinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
1
12
0
1
Order By: Relevance
“…1 H and 13 C NMR data of 4 (Table ) were nearly identical to those of compounds 1 − 3 with the exception of resonances corresponding to the monooxygenated farnesyl group attached to C-3. On the other hand, the NMR data resembled those of the sesquiterpene unit of mutisiphenone B, isolated previously by us from M. friesiana . The presence of duplicated signals for certain carbons and for H-6‘, H-10‘, and Me-12‘ protons (Table ) indicated that compound 4 was a mixture of diastereomers (epimers at C-3 or C-8‘).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…1 H and 13 C NMR data of 4 (Table ) were nearly identical to those of compounds 1 − 3 with the exception of resonances corresponding to the monooxygenated farnesyl group attached to C-3. On the other hand, the NMR data resembled those of the sesquiterpene unit of mutisiphenone B, isolated previously by us from M. friesiana . The presence of duplicated signals for certain carbons and for H-6‘, H-10‘, and Me-12‘ protons (Table ) indicated that compound 4 was a mixture of diastereomers (epimers at C-3 or C-8‘).…”
Section: Resultssupporting
confidence: 74%
“…On the other hand, the NMR data resembled those of the sesquiterpene unit of mutisiphenone B, isolated previously by us from M. friesiana. 7 The presence of duplicated signals for certain carbons and for H-6′, H-10′, and Me-12′ protons (Table 2) indicated that compound 4 was a mixture of diastereomers (epimers at C-3 or C-8′). The isolation of 5-methylcoumaranones A-D (1-4) together with structurally related 5-methylcoumarins and 5-methylphenones 7 containing mono-and sesquiterpene residues enabled us to suggest a biosynthetic relationship between these three groups of compounds in the shrub M. friesiana (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on information from the two biochromatograms shown in Figures 1 and 2, material correlated with bioactivity as well as material suggested by LC-PDA-HRMS to be prenyl-or geranyl coumarin derivatives were isolated by preparative-scale HPLC followed by analytical-scale HPLC as detailed in the Materials and Methods section. This led to isolation of the new compounds 2, 5, 6, 8, 10, 11, 14, 15, 17-19, and 23-25 as well as identification of the known compounds marmesin (1) [28], 7-demethylsuberosin (3) [29], apigravin (4) [30], bothrioclinin (7) [31], (+)-2-[(2R)-6-acetyl-2,3-dihydro-5-hydroxybenzofuran-2-yl]-prop-2-enyl 15-methylbutanoate (8) [29], 3,5-bis-(isopent-2-en-1-yl)-4-hydroxyacetophenone (9) [32], 6-acetyl-2,2-dimethyl-8-(3-methylbut-2-en-1-yl)-2H-chromene (12) [33], and mutisicoumarin B (16) [34] by comparison of their 1 H NMR data with data from the literature. Retention times, HRESIMS, and 1 H NMR data for 1, 3, 4, 7-9, and 12 are given in Table S1 .…”
Section: Structure Elucidation Of Prenyl-and Geranyl Coumarin Derivatmentioning
confidence: 99%
“…Compound 2 is a new compound for which the name gerbeloid 1 is proposed. [33], and mutisicoumarin B (16) [34] by comparison of their 1 H NMR data with data from the literature. Retention times, HRESIMS, and 1 H NMR data for 1, 3, 4, 7-9, and 12 are given in Table S1, Supplementary Material.…”
Section: Structure Elucidation Of Prenyl-and Geranyl Coumarin Derivatmentioning
confidence: 99%